Terroir and Territory on the Colonial Frontier: Making New-Old World Wine in the Holy Land. (April 2020) - Monterescu, Daniel; Handel, Ariel
Abstract: Etymologically related, the concepts of terroir and territoriality display divergent cultural histories. While one designates the palatable characteristics of place as a branded story of geographic distinction, the other imbues the soil with political meaning. This paper traces the production of eno-locality in a contested space on both sides of the Green Line in Israel/Palestine. The case of the Yatir award-winning winery shows how terroir and territory are blended in the political economy and cultural politics of colonial place-making. Located on a multiscalar frontier—climatic, geopolitical, and viticultural—Yatir Winery positions itself simultaneously within the Mediterranean transnational landscape and in a biblical site of historical authenticity. Enacting strategic regimes of signification to target the increasing demand for high-end wines on both the global and local markets, it makes a claim for place, while appropriating Palestinian land and redefining ancient Jewish heritage. The result articulates a settler colonial landscape whose symbolic and material transformations are reflected in the Israeli search for rooted identity. Analytically, we explore the power of border and frontier wines to reconfigure the differences between New World and Old World paradigms. We conclude by outlining a comparative framework of the charged relations between terroir and territory that articulates the nexus between border typologies and the colonial politics of wine.